15 anos de investigação em contabilidade de gestão estratégica: uma meta-análise - Pires, Rui A.R. (2018)
The main purpose of this paper is to analyse and understand the evolution of the strategic management accounting (SMA) literature by performing a meta-analysis of literature and critiquing of SMA papers published in the leading journals in the field covering fifteen years: 2000-2014 inclusive. We performed a descriptive meta-analysis of 43 SMA papers published in five top ranked accounting journals in order to provide a broad perspective of the field. We use a method and techniques previously employed in the field of management accounting to select and classify the papers. The main findings presented in the paper provide some light about the main topics studied, research settings, theories, methods, and primary data analysis used in SMA research. Therefore, this paper extends upon the previous literature reviews, by extending the scope and the time frame. In addition, this paper provides a meta-analysis of the SMA literature never done before in the field of the SMA.